The Effect of Spatial Organization on the Sustainability of the Neighborhood Unit in the Residential Environment (Journal of Engineering, 2012)
Contemporary residential neighborhoods suffer from weak sustainability of urban residential environments as a result of the adoption of inefficient spatial organization at the neighborhood unit level. This resulted negative characteristics which affected the achievement of sustainable development plans for the residential environment that constitute the majority of the urban fabric of cities.The physical affordances ,within the vocabulary of recent times,overcame the spiritual ones and affected the residential environment. Accordingly,the concept of space changed in contemporary residential areas through the dominance of the physical aspect (mass) on the symbolic aspect (space).The modern technology occupied an important level being one of the basic features of the era. Therefore, achieving sustainability at the urban level of the residential environment requires an efficient spatial organization which ensures the linking of urban space with the surroundings, and the new services together with the basic ones that need maintenance and rehabilitation.The weak sustainability of the built residential environment constitutes the main research problem. This problem results from the inefficiency of space organization at the neighborhood unit level. The research aims to establish spatial organized mechanisms at the neighborhood unit level that would achieve sustainability through the investment of sustainable factors of traditional residential environment in the planning and design of modern neighborhood,as well as the adoption of human design strategies to raise the efficiency of spatial organization.The research stems for a hypothesis that states (the efficient spatial organization at the  neighborhood unit level produces a sustainable urban environment at the level of larger residential neighborhood).